2003
DOI: 10.1046/j.1365-2095.2003.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gossypol from dietary cottonseed meal on haematology, reproductive steroids and tissue gossypol enantiomer concentrations in male rainbow trout (Oncorhynchus mykiss )

Abstract: Rainbow trout (Oncorhynchus mykiss) males were fed, during a 9‐month period, five experimental diets where fishmeal proteins were gradually replaced with cottonseed meal (CS) proteins (0, 25, 50, 75 and 100%; diets 1–5, respectively). This study was carried out to evaluate the action and tissue concentrations of gossypol. Growth performance of fish was not affected with the increasing levels of CS in the diets. Haemoglobin concentration and haematocrit significantly decreased in fish fed 100% CS compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 35 publications
5
20
0
1
Order By: Relevance
“…The same growth performance and feed utilization were observed under these conditions as fi sh fed a complete FM diet during outdoor culture. Large rainbow trout (1.5 year old adults and broodstock) fed CM-containing feed for more than 9 months do not show depressed growth (Dabrowski et al, 2000;Blom et al, 2001;Rinchard et al, 2003;Lee et al, 2006). In contrast, lower growth was observed in both sexes of mature tilapia ( Oreochromis sp.)…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The same growth performance and feed utilization were observed under these conditions as fi sh fed a complete FM diet during outdoor culture. Large rainbow trout (1.5 year old adults and broodstock) fed CM-containing feed for more than 9 months do not show depressed growth (Dabrowski et al, 2000;Blom et al, 2001;Rinchard et al, 2003;Lee et al, 2006). In contrast, lower growth was observed in both sexes of mature tilapia ( Oreochromis sp.)…”
Section: Discussionmentioning
confidence: 96%
“…The anti-nutritional eff ect of gossypol is not only determined by its toxicity but by its interaction with other nutrients. The ε-amino group of lysine combines with the reactive aldehyde group of gossypol to form a Schiff base, which lowers lysine bioavailability (Rinchard et al, 2003). Depressed growth was reported in juvenile and broodstock rainbow trout fed CM containing >300 μg/g and 463 μg/g free gossypol, respectively (Lee Herman, 1970;Blom et al, 2001;Rinchard et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We measured serum BUN and UA levels to evaluate kidney function and AST, ALT, ALB, and TP levels for liver function (Travlos et al, 1996). The liver is a main organ of FG metabolism (Rinchard et al, 2003) while the egg white proteins are continuously synthesized in the oviduct. We also assessed the kidney, liver, and oviduct structure by histopathological analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Rinchard et al. () fed rainbow trout for 9 months with feeds prepared using cottonseed pulp as replacement of fishmeal at increasing ratios of 0%, 25%, 50%, 75%, and 100%. At the end of the experiment, they found that the levels of haemoglobin and hematocrit significantly decreased as the proportion of plant protein in the diet increased.…”
Section: Discussionmentioning
confidence: 99%